(untitled) (Innovaciones Educativas, 2020)
Student academic performance is an essential factor in the quality of education provided by a university. To assess the incidence of factors on academic performance and the quality of education of the students of seven faculties of the Chimborazo Polytechnic School (Riobamba, Ecuador) is the objective of this research. The research design was descriptive, cross-sectional, and non-experimental, relying on a quantitative and qualitative approach; the field study instrument was a structured survey with closed questions applied to a sample of 375 students, based on a student population of 15,032 people. The article is also founded on a bibliographic and documentary study. The results revealed that the most significant factors and the ones with the most incidence on the academic performance and that determined the quality of education the students received were: socioeconomic (30%), family (25%), school-academic (23%), and personal (22%),. Therefore, it is concluded that 95% of the investigated students considered that the analyzed factors directly affect their academic performance and the education received